FOXO1 Gene Downregulation and Promoter Methylation Exhibits Significant Correlation With Clinical Parameters in Indian Breast Cancer Patients - Khan, Mohammad Aasif; Massey, Sheersh; Ahmad, Irfan; Sadaf,; Akhter, Naseem; Habib, Maria; Mustafa, Saad; Deo, S. V. S.; Husain, Syed Akhtar (Frontiers in Genetics, 2022)
Background: Forkhead box ‘O’ 1 which is member of Forkhead box family of transcription factors is known to play key role in different physiological processes including cell cycle arrest, autophagy and apoptosis. FOXO1 is defined to play tumor suppressive role in various malignancies including breast cancer and its Dysregulation is frequently reported. However, the evaluation of FOXO1 promoter methylation and its expression at mRNA and protein level in different stages of breast cancer and its association with different clinical parameters is still not done. Therefore, for better understanding the role of FOXO1 in breast cancer, in our study we examined the FOXO1 mRNA and protein expression in Breast cancer samples of Indian breast cancer patients. Results: Total 127 breast cancer samples along with adjacent normal tissue (n=127) were analyzed through methylation (MS-PCR), mRNA expression (Real-time PCR) and Immunohistochemistry (IHC). We detected 69.29% cases to be downregulated at the mRNA level, and 77.95% of cases exhibited no or low protein expression. In our data we report a significant association (p= 0.0001) between the downregulated protein expression and promoter hypermethylation of FOXO1 gene. We also found a significant correlation of FOXO1 mRNA level with Age (p= 0.008), age at first live birth (p= 0003), tumor size (p= 0.05) and lymph node status (p=0.01). Conclusion: we in our study report the tumor suppressive role of FOXO1 in case of Indian breast cancer patients and our data suggest it to exhibit prognostic importance. However, further research is needed to evaluate FOXO1 significance in diagnostic and therapeutic targeting in breast cancer cases.